Sediment colour reflectance spectroscopy as a proxy for wet/dry cycles at Lake El'gygytgyn, Far East Russia, during Marine Isotope Stages 8 to 12. Issue 6 (15th April 2014) - Wei, Jeremy H.; Finkelstein, David B.; Brigham‐Grette, Julie; Castañeda, Isla S.; Nowaczyk, Norbert; Ariztegui, Daniel
Abstract Marine Isotope Stage 11 has been proposed as an analogue for the present interglacial interval; yet, terrestrial climate records from both this region and time interval are rare. The sediments deposited at Lake El'gygytgyn (67°30′N, 172°5′E) in Far East Russia contain a 3·56 Ma record of climate variability. This study presents a high‐resolution record of sediment colour change from Marine Isotope Stage 8 to 12 (ca 275 to 475 ka) and demonstrates the link between lake catchment processes and climate variability. The hue colour parameter, calculated from data collected via colour reflectance spectroscopy in the visible spectrum (380 to 720 nm), exhibits correspondence with global climate records. Determining the source of sediment colour changes was achieved through detailed mineralogical and sedimentological methods, and linked to colour changes through a series of colour sensitivity tests. Mineralogical data, measured by X‐ray diffraction, reveal fluctuations in concentrations of clay minerals corresponding to colour changes. Further analyses of the clay mineral assemblages show no change in relative clay mineral abundances, yet demonstrate a lake catchment dominated by physical weathering processes. Using measured mineral abundances, reconstructions of sediment colour based on colour reflectance mineral standards link mineral and clay mineral content to overall sediment colour. Colour sensitivity tests demonstrate the ability of iron oxide minerals to stain sediments red. Additionally, colour sensitivity to organic matter content was tested, suggesting that organic content drives variability in the red portion of the spectrum and darkens the overall colour signal. Sediment colour is then ultimately linked to physical weathering of bedrock minerals, with small amounts of chemical weathering producing iron oxides during wet intervals. Fluctuations in the sediment colour reveal a high‐resolution record of wet/dry cycles, and provide new information about wet periods for the Russian Arctic region not yet understood from other lake proxy records.